Perbedaan Perkembangan Verbal Antara Anak Usia 3-5 Tahun Yang Diasuh Orang Tua Sendiri dengan Anak Usia 3-5 Tahun yang Diasuh di Tempat Penitipan Anak - Vandasari, Lia, Prof. Dr. Bambang Soebagyo, dr. Sp.A (K) (2015)
Background: Early childhood stimulation can be provided by parents or daycare. Stimulation by parents and daycare can be seen from parenting in influencing aspects of child development, including the development of verbal. With Denver II children can be seen delayed verbal or not. Objectives: 1) To determine the verbal development of children aged 3-5 years are taken care of their own parents and are cared for in daycare. 2) To compare the differences in verbal abilities of children aged 3-5 years who cared for the child's own parents with children aged 3-5 years are cared for in daycare. Methods: The method used is observational analytic design with cross sectional analytic approach. The subjects of the study children aged 3-5 years who raised himself in Pabelan Surakarta and toddlers aged 3-5 years are taken care of in a landfill Madani with samples each of 42 toddlers. Data analysis using Chi Square with p = 0.05. Results: Based on the chi-square test results showed that the p value of 0.000 <0.05. With this, there are differences in verbal abilities of children aged 3-5 years who cared for the child's own parents with children aged 3-5 years are cared for in daycare. Verbal development of children are taken care of in a landfill Madani better than those cared for by the parents themselves. Conclusions: There are differences in verbal abilities of children aged 3-5 years who cared for the child's own parents with children aged 3-5 years are cared for in daycare